A Conceptual Model of Entrepreneurship as Firm Behavior - Covin, Jeffrey G.; Slevin, Dennis P. (Entrepreneurship Theory and Practice, 1991)
This article outlines a conceptual model of entrepreneurship as an organizational-level phenomenon. The model is intended to depict the organizational system elements that relate to entrepreneurial behavior among larger, established firms, but may also be applicable in varying degrees to many smaller firms. Entrepreneurship is described as a dimension of strategic posture represented by a firm's risk-taking propensity, tendency to act in competitively aggressive, proactive manners, and reliance on frequent and extensive product innovation. The proposed model delineates the antecedents and consequences of an entrepreneurial posture as well as the variables that moderate the relationship between entrepreneurial posture and firm performance. The advantages of a firm-behavior perspective on entrepreneurship are discussed, as are the theoretical and managerial implications of such a perspective.